2004
DOI: 10.1007/s00441-004-0990-7
|View full text |Cite
|
Sign up to set email alerts
|

Human embryonic germ cells isolation from early stages of post-implantation embryos

Abstract: Human embryonic germ (hEG) cell is a very important alternative pluripotent stem cell resource. We describe the derivation of hEG cells from human embryonic fetal gonads over 6-8 weeks postconception. A large number of EG-like cell clumps were obtained at passage 1 and thus facilitated the following routine culture when the donor tissues were trypsinized with gentle pipetting and plated on feeder layer cells in the initial culture. Eight diploid hEG cell lines have been cultivated in vitro for extended periods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 39 publications
0
49
0
3
Order By: Relevance
“…As shown in Fig. 3, the gonocyte colonies were stained positive for Oct-4, SSEA-4, and c-Kit, suggesting that these colonies share similar pluripotent markers as well as embryonic germ cells (EGCs) that were cultured from PGCs (Shamblott et al 1998, Turnpenny et al 2003, Liu et al 2004, Park et al 2004, Pan et al 2005. The result also showed that the cultured gonocyte colonies were only dotted stained with c-Kit, suggesting that the c-Kit might be down-regulated in the present culture system.…”
Section: Scf Affects the Morphology Of Human Gonocytes In Vitromentioning
confidence: 89%
“…As shown in Fig. 3, the gonocyte colonies were stained positive for Oct-4, SSEA-4, and c-Kit, suggesting that these colonies share similar pluripotent markers as well as embryonic germ cells (EGCs) that were cultured from PGCs (Shamblott et al 1998, Turnpenny et al 2003, Liu et al 2004, Park et al 2004, Pan et al 2005. The result also showed that the cultured gonocyte colonies were only dotted stained with c-Kit, suggesting that the c-Kit might be down-regulated in the present culture system.…”
Section: Scf Affects the Morphology Of Human Gonocytes In Vitromentioning
confidence: 89%
“…To date, six laboratories have reported successful derivation of human EGC lines (Shamblott et al, 1998;Turnpenny et al, 2003;Liu et al, 2004;Park et al, 2004;He et al, 2007;Hua et al, 2009). This very limited number of groups is due to the difficulties of acquiring human PGCs (therapeutic termination of pregnancy and ethical approval is needed), and the complexity of the derivation and culture of EGCs (Turnpenny et al, 2006;Kerr et al, 2006;Perret et al, 2008).…”
Section: Human Eg Cellsmentioning
confidence: 99%
“…Although it is a clonal cell line, there are several phenotypic variations in STO cells from different isolates or even depending on the time in culture that affects the human EGC derivation (Kerr et al, 2006). Some groups have also successfully utilized primary MEFs (CF1) as feeder layers for EGC derivation (Liu et al, 2004;Hua et al, 2009) and even human embryonic fibroblast-like cells derived from gonadal ridges and dorsal mesenteries (see below, He et al, 2007). The feeder layer can be mitotically inactivated with mitomycin C or by irradiation, either before or after plating.…”
Section: Feeder Layermentioning
confidence: 99%
See 2 more Smart Citations